Northern and Eastern Enlargement of EMU: Do Structural Reforms Matter? - Andrew Hughes Hallett; Svend E Hougaard Jensen; Christian Richter (SUERF - The European Money and Finance Forum, 2004)
This paper studies the incentives to join or enlarge a monetary union under alternative assumptions about the extent of market reform within the union and in candidate countries. Lack of labour mobility, wage/price flexibility or fiscal reform brings costs for both new entrants and in the existing union. Countries will only want to join a union where there has been sufficient reform, and where markets are more flexible than their own. But existing members will want the same properties of their new partners as well. Fiscal restrictions, or a lack of fiscal flexibility, will exaggerate this incentive mismatch and may delay the necessary reforms.
Keywords: F2; F15; F33; F42; 330; EMU; Enlargement; Structural Flexibility; Fiscal Policy; Eurozone; EU-Mitgliedschaft; Wirtschaftsreform; Deregulierung; EU-Staaten; Großbritannien; Osteuropa